Looking toward the Manufactures and Machinery Buildings from the Agriculture Building, Alaska-Yukon-Pacific Exposition, Seattle, Washington, November 1908 - Nowell, Frank H., 1864-1950 (1908)
On verso of photograph: A view from the steps of the Agriculture Building in November 1908 PH Coll 727.456 To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number